2003
DOI: 10.1007/s00412-003-0261-5
|View full text |Cite
|
Sign up to set email alerts
|

Chromosome painting in Callicebus lugens , the species with the lowest diploid number (2 n =16) known in primates

Abstract: Cytogenetic studies have shown that New World primates are karyologically diverse and highly derived. The genus Callicebus is the best example of this karyological diversity, with diploid numbers ranging from 2n=50 to 2n=16. We report on Callicebus lugens, which has the lowest diploid number (2n=16) yet found in the primate order and represents a striking example of extreme karyotypic shuffling. To better understand the genomic rearrangements that have resulted in this extremely low diploid number, we mapped c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
55
0
8

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(67 citation statements)
references
References 23 publications
(29 reference statements)
2
55
0
8
Order By: Relevance
“…42). However, in this case, detailed cytogenetic analysis by using FISH shows that despite the diversity and the rearranged karyotype, the synteny of 11 human chromosomes is maintained intact in Callicebus callicebus (43). At this point, it is therefore hard to conclude on the potential generality of chromosomespecific regulatory functions.…”
Section: Discussionmentioning
confidence: 87%
“…42). However, in this case, detailed cytogenetic analysis by using FISH shows that despite the diversity and the rearranged karyotype, the synteny of 11 human chromosomes is maintained intact in Callicebus callicebus (43). At this point, it is therefore hard to conclude on the potential generality of chromosomespecific regulatory functions.…”
Section: Discussionmentioning
confidence: 87%
“…Callicebus lugens is the species with the most derived karyotype and lowest diploid number of chromosomes found among all primates. Chromosome painting has been applied to six Callicebus species -Callicebus moloch, C. lugens, C. cupreus, C. pallescens, C. d. pallescens and C. personatus (Stanyon et al 2000(Stanyon et al , 2003Barros et al 2003;Dumas et al 2005;Rodrigues et al 2011) -showing that fusions are the predominant rearrangements responsible for the karyotype evolution of these species; moreover, it has been shown that three new human associations, 7/15, 10/11 and 22/2, and two inversions involving the 2/22 (22/2/22) and 16/2 human associations (16/2/16/2), characterize the hypothetical ancestral Callicebus karyotype (Figure 2 (c)). Apart from these ancestral associations shared by all of the species analyzed, further comparison permits the identification of other specific associations and arrangements, such as: 12/19 linking all species but C. lugens; 13/17 present in C. cupreus, C. pallescens, and C. d. pallescens; 17/20 association present in all species except C. d. pallescens, C. personatus and C. moloch; 9/7/5a shared by C. cupreus and C. d. pallescens (not reported in Figure 2).…”
Section: Pitheciidae Familymentioning
confidence: 99%
“…This outcome could be understood by proposing that shorter sequences increased the probability of obtaining evolutionary independent loci in genomes subjected to extensive chromosomal shuffling, such as NP. For instance, in Callicebus lugens , with a diploid number of 16 chromosomes (Bonvicino et al., 2003), genomic contraction has been prominent, with most human chromosome probes painting four large chromosome pairs (Stanyon, Bonvicino, Svartman, & Seuanez, 2003). This extreme level of karyotypic rearrangement might be explained by duplication of two ancestral NP syntenies (2b/16a and 10b/16b), six fissions, one inversion, and 31 fusion events for deriving the karyotype of Callicebus lugens from the presumed ancestral NP karyotype with 2 n  = 54 (Figure 6).…”
Section: Discussionmentioning
confidence: 99%